PENINGKATAN HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN SENI RUPA MELALUI MODEL PJBL BERBANTUAN MEDIA PPT INTERAKTIF DI SD ADVENT KOTA KUPANG - Fallo, Elisabeth Nova Ekasari; Ga, Paulina Riwu; Benu, Adam Bol Nifu (Universitas Nusa Cendana, 2024)
This study aims to improve the learning outcomes of fourth-grade students at SD Adventist Kupang City on the material for making decorative study schedules by applying the Project Learning model. This research is a class action research carried out in two cycles with the following teps: planning, implementing, observing, and reflecting. The subjects in this study were 15 class IV students. The data collection instruments used in this study were teacher observation sheets, student observation sheets, students' project skills, and learning achievement tests. The data were analyzed descriptively qualitatively and quantitatively.The results showed that there was an increase in student learning outcomes in each cycle. Student learning outcomes increased in cycle I, namely 27% increased to 100% in cycle II, project work results increased from 20% to 100% in cycle II, teacher observation results increased in cycle I 58% in cycle II to 100% and the results of student observations increased in cycle I 58,5% to 87% in cycle II. Thus it can be concluded that the application of the Project Based Learning learning model in learning can improve the learning outcomes of fourth-grade students in the material for making decorative lesson schedules at Adventist Elementary School, Kupang City.